A genetic study of Attention-Deficit Hyperactivity Disorder, Conduct Disorder, Oppositional Defiant Disorder and Reading Disability: Aetiological overlaps and implications - Martin, Neilson; Levy, Florence; Piek, Jan; Hay, David (Routledge, 2006)
Attention Deficit Hyperactivity Disorder (ADHD) commonly co-occurs with Oppositional Defiant Disorder, Conduct Disorder and Reading Disability. Twin studies are an important approach to understanding and modelling potential causes of such comorbidity. Univariate and bivariate genetic models were fitted to maternal report data from 2040 families of twins from the Australian Twin ADHD Project. All measures showed a heritability of over 0.8 and little role for the common family environment, except for the combined subtype of ADHD with a heritability of 0.69 and a common environment of 0.19. About one-third of the genetic variance in ADHD was shared with the other behaviours, the largest overlap being with Oppositional Defiant Disorder. Common environmental effects were shared between the combined ADHD subtype and the other measures. Some implications of these findings for home and school are discussed.